THE PHILOSOPHY OF ECONOMICS: SUBJECT AND METHOD - Ильин, В. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The problem of philosophy of economics as the new discipline, its actuality and necessity for social sciences are observed.